Cytotoxic and anticancer properties of the Malaysian mangrove pit viper (Trimeresurus purpureomaculatus) venom and its disintegrin (purpureomaculin) - Tan, Choo Hock (J Venom Anim Toxins Incl Trop Dis, 2020)
BACKGROUND: The Asiatic pit vipers from the Trimeresurus complex are medically important venomous snakes. These pit vipers are often associated with snakebite that leads to fatal coagulopathy and tissue necrosis. The cytotoxic venoms of Trimeresurus spp.; however, hold great potential for the development of peptide-based anticancer drugs. METHODS: This study investigated the cytotoxic effect of the venom from Trimeresurus purpureomaculatus, the mangrove pit viper (also known as shore pit viper) which is native in Malaysia, across a panel of human cancer cell lines from breast, lung, colon and prostate as well as the corresponding normal cell lines of each tissue. RESULTS: The venom exhibited dose-dependent cytotoxic activities on all cell lines tested, with median inhibition concentrations (IC(50)) ranging from 0.42 to 6.98 µg/mL. The venom has a high selectivity index (SI = 14.54) on breast cancer cell line (MCF7), indicating that it is significantly more cytotoxic toward the cancer than to normal cell lines. Furthermore, the venom was fractionated using C(18) reversed-phase high-performance liquid chromatography and the anticancer effect of each protein fraction was examined. Fraction 1 that contains a hydrophilic low molecular weight (approximately 7.5 kDa) protein was found to be the most cytotoxic and selective toward the breast cancer cell line (MCF7). The protein was identified using liquid chromatography-tandem mass spectrometry as a venom disintegrin, termed purpureomaculin in this study. CONCLUSION: Taken together, the findings revealed the potent and selective cytotoxicity of a disintegrin protein isolated from the Malaysian T. purpureomaculatus venom and suggested its anticancer potential in drug discovery.